Approaching the Most Economic Preparation of Hole Transport Layer by Organic Monomolecular Strategy for Efficient Inverted Perovskite Solar Cells. Issue 6 (13th May 2020) - Liu, Hui; Liu, Changwen; Li, Wang; Kong, Weiguang; Chen, Hong; Zhang, Haichao; Zhang, Xian; Wang, Weijun; Cheng, Chun
Abstract : Hole transport materials and their processing occupy at least one‐third of the cost of perovskite solar cells (PSCs), which leaves plenty of room to improve the process of device fabrication. Herein, a facile immersing and washing strategy (I‐method) is reported to prepare effective organic monomolecular layers (MLs) of poly[ N, N ′‐bis(4‐butylphenyl)‐ N, N ′‐bis(phenyl) benzidine] (polyTPD) as hole transport layers (ML‐HTLs) to construct cost‐effective planar inverted PSCs. The ML enables an enhanced wettability to perovskite precursors and thus results in the growth of compact and uniform perovskite films. In addition, the ML exhibits better energy‐level alignment with perovskite. Consequently, the ML‐polyTPD‐based PSCs deliver significantly enhanced power conversion efficiency (PCE) and reproducibility, as compared to that of pristine polyTPD based devices. The practical consumption of polyTPD during the I‐method is cut to the bone, with the cost of 0.8 for 1 m 2 substrate being achieved, which is 0.15% of that by S‐method. The developed I‐method is facile, and time‐ and cost‐saving with low requirement for facilities as well as with low temperature and solution processability. This strategy is cost‐effective to prepare ML‐HTLs for large‐area and flexible PSCs with competitive photovoltaic performance and enhanced reproducibility. Abstract : A facile immersing and washing strategy (I‐method) is reported to prepare effective organic monomolecular layers (MLs) as hole transport layers (ML‐HTLs). The I‐method can largely reduce the process cost as well as realize batch preparation of ML‐HTLs. Perovskite solar cells based on ML‐HTLs show improved power conversion efficiency and stability.